Stoichiometric sample parameters from boreal peat at FN-Land_2022_SiikanevaPeatland_20221005 - Böhm, Marianne; Baysinger, Mackenzie; Treat, Claire C (PANGAEA, 2025)
This dataset reports basic chemical and physical characteristics measured in intact sphagnum and peat samples sourced from a boreal peatland complex (Siikaneva Bog, Finland). These were used in an incubation experiment to investigate reactions greenhouse gas production to nitrogen amendments (see adjacent dataset.) Shallow peat samples were extracted in bulk with a bread knife in October 2022 from a homogeneous sphagnum lawn at three locations within several meters distance. Three soil horizons were distinguished according to the position of the water table: above (0-3 cm), fluctuating (3-7 cm) and below the water table (7-20 cm). Three spatial replicates were united per layer and stored at 4°C until the experiment started. Data in this table were measured in material that was set aside at experiment setup and stored in a freezer. The dataset contains gravimetric water content, total and organic carbon and nitrogen contents (soliTOC cube, elementar Analysensysteme / exceed rapid maxN). From another subsample, water was extracted with Rhizon samplers to probe pH and electric conductivity and determine dissolved organic carbon (elementar Analysensysteme / TOC-L analyzer with TNM-1 module, Shimadzu). Bulk density values used in the experiment were estimated from Schwarzer et al. (2023) but provided here for completeness.